2017
DOI: 10.3389/fmicb.2017.01106
|View full text |Cite
|
Sign up to set email alerts
|

Marine Rare Actinobacteria: Isolation, Characterization, and Strategies for Harnessing Bioactive Compounds

Abstract: Actinobacteria are prolific producers of thousands of biologically active natural compounds with diverse activities. More than half of these bioactive compounds have been isolated from members belonging to actinobacteria. Recently, rare actinobacteria existing at different environmental settings such as high altitudes, volcanic areas, and marine environment have attracted attention. It has been speculated that physiological or biochemical pressures under such harsh environmental conditions can lead to the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 158 publications
0
94
1
1
Order By: Relevance
“…Actinobacteria were dominant here (Figure 1), which is in line with knowledge of their inherent flexibility by virtue of harbouring wide metabolic capacities and survival mechanisms (12, 15, 20), thus giving them the selective advantage to dominate over other phyla in harsh environments. This phenomenon is not exclusive to just arid deserts but many other extreme environmental settings such as volcanic areas, dark caves and marine environments (6567). The Actinobacteria community in these extreme habitats were found to produce various broad-spectrum antibiotics, enzymes, anti-tumor agents and immunomodulators.…”
Section: Resultsmentioning
confidence: 99%
“…Actinobacteria were dominant here (Figure 1), which is in line with knowledge of their inherent flexibility by virtue of harbouring wide metabolic capacities and survival mechanisms (12, 15, 20), thus giving them the selective advantage to dominate over other phyla in harsh environments. This phenomenon is not exclusive to just arid deserts but many other extreme environmental settings such as volcanic areas, dark caves and marine environments (6567). The Actinobacteria community in these extreme habitats were found to produce various broad-spectrum antibiotics, enzymes, anti-tumor agents and immunomodulators.…”
Section: Resultsmentioning
confidence: 99%
“…Streptomyces sp. DSM 14386 produced five new compounds (17)(18)(19)(20)(21) in medium supplemented with 1.5% NaCl, while this strain produced two brominated congeners (22,23) in medium containing 1.5% NaBr [42]. Similarly, a novel antibacterial cyclodepsipeptide, named NC-1 (24), was produced by a red soil-derived strain Streptomyces sp.…”
Section: The Osmac Approach Mediated By Co-culturementioning
confidence: 99%
“…However, the emergence of antibiotic-resistant pathogens or drug-resistant disease conditions and most of the NPs are not produced in significant titers or the biosynthetic gene clusters (BGCs) are cryptic, or the producer strains are not genetically tractable, which pose the greatest challenge for NPs based drug discovery [16][17][18]. In such cases production can be achieved in other production platforms as genetically tractable alternative hosts or suitable heterologous hosts [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if not all microorganisms may be cultivated by classical microbiological approaches, technologies that have enabled their genetic material to be accessed and explored have grown exponentially in recent years and have granted researchers novel tools for the study and exploitation of these genomes to diverse ends 7 . Metagenomic studies have been of great importance to uncover proteins with superior industrial properties 8 , rare bioactive compounds 9 , and even novel genetic parts for the construction of reliable synthetic circuits in non-conventional bacterial hosts 10 ; moreover, studies from the metagenome of contaminated sites have revealed novel pathways for the degradation of heavy metals 11 , toxic chemicals 12 , as well as innovative mechanisms that enable microorganisms to thrive in the most hostile environments 13 , which can be tapped to grant industrially relevant microorganisms the ability to perform under the harsh conditions needed for efficient fermentation conditions.…”
Section: Introductionmentioning
confidence: 99%